Are new models needed to optimize the utilization of new medicines to sustain healthcare systems?. Issue 1 (January 2014) - Godman, Brian; Malmström, Rickard E; Diogene, Eduardo; Gray, Andy; Jayathissa, Sisira; Timoney, Angela; Acurcio, Francisco; Alkan, Ali; Brzezinska, Anna; Bucsics, Anna; Campbell, Stephen M; Czeczot, Jadwiga; et al.
<x xml:space="preserve">Abstract</x> Medicines have made an appreciable contribution to improving health. However, even high-income countries are struggling to fund new premium-priced medicines. This will grow necessitating the development of new models to optimize their use. The objective is to review case histories among health authorities to improve the utilization and expenditure on new medicines. Subsequently, use these to develop exemplar models and outline their implications. A number of issues and challenges were identified from the case histories. These included the low number of new medicines seen as innovative alongside increasing requested prices for their reimbursement, especially for oncology, orphan diseases, diabetes and HCV. Proposed models center on the three pillars of pre-, peri- and post-launch including critical drug evaluation, as well as multi-criteria models for valuing medicines for orphan diseases alongside potentially capping pharmaceutical expenditure. In conclusion, the proposed models involving all key stakeholder groups are critical for the sustainability of healthcare systems or enhancing universal access. The models should help stimulate debate as well as restore trust between key stakeholder groups.